2012
DOI: 10.1248/bpb.35.171
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Mechanisms of the Hepatoprotective Effect of Gomisin A against Oxidative Stress and Inflammatory Response in Rats with Carbon Tetrachloride-Induced Acute Liver Injury

Abstract: Oxidative damage and inflammation are implicated in the pathogenesis of liver injury and fibrosis. In the present study, we investigated the molecular mechanism by which gomisin A conferred a hepatoprotective effect, focusing on its antioxidant and anti-inflammatory effects using rats with carbon tetrachloride (CCl 4 )-induced acute liver injury. Pretreatment with gomisin A prior to the administration of CCl 4 markedly prevented an increase in alanine aminotransferase, aspartate aminotransferase, and histologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…et Wils., is a well-known traditional Chinese herb that is widely used as a tonic or adjuvant drug in Asia (Panossian and Wikman, 2008). Numerous studies have demonstrated the potent, beneficial effect of Schisandra sphenanthera on immunity and heart and kidney function as well as for hepatoprotection against chemical hepatitis and various hepatotoxins (Zhu et al, 2000;Panossian and Wikman, 2008;Teraoka et al, 2012). Wuzhi tablet (WZ), an ethanol extract preparation of Schisandra sphenanthera, is commonly used for the treatment of chronic viral hepatitis and liver dysfunction in a clinical setting, and is indexed in the pharmacopoeia of the People's Republic of China .…”
Section: Introductionmentioning
confidence: 99%
“…et Wils., is a well-known traditional Chinese herb that is widely used as a tonic or adjuvant drug in Asia (Panossian and Wikman, 2008). Numerous studies have demonstrated the potent, beneficial effect of Schisandra sphenanthera on immunity and heart and kidney function as well as for hepatoprotection against chemical hepatitis and various hepatotoxins (Zhu et al, 2000;Panossian and Wikman, 2008;Teraoka et al, 2012). Wuzhi tablet (WZ), an ethanol extract preparation of Schisandra sphenanthera, is commonly used for the treatment of chronic viral hepatitis and liver dysfunction in a clinical setting, and is indexed in the pharmacopoeia of the People's Republic of China .…”
Section: Introductionmentioning
confidence: 99%
“…(f) Nutrients BCAA-enriched diet in DEN treated rats (Cha et al 2013) Decreased mRNA levels for markers of fibrosis, angiogenesis, and apoptosis inhibition LA in TAA-treated rats (Foo et al 2011) Reduction in cirrhosis incidence, hepatic fibrosis, and AST/ALT activities Omega-3 in CCl4-treated rats (Shaaban et al 2014) Counteracting hepatic oxidative stress and augmenting hepatic antioxidants, reducing α-SMA expression, down-regulating PDGF-β expression, and inhibiting the fibrogenesis response (g) Traditional Chinese medicine In CCL4-induced fibrosis model, Panax notoginseng, Huisheng oral solution, saikosaponin-d, hydroxysafflor yellow A, Paeonia lactiflora and Astragalus, dahuangzhechong pills, and gomisin A were effective (Cai et al 2010;Dang et al 2007;Li et al 2014c;Peng et al 2009b;Sun et al 2007;Teraoka et al 2012;Zhang et al 2012) Reduced inflammatory cytokines, alleviated liver fibrosis…”
Section: Resultsmentioning
confidence: 99%
“…Mouse Gene Forward primer Reverse primer mGRP78 mCHOP mXBP-1 mTNF-α mIL-6 mMCP-1 GAAAGGATGGTTAATGATGCTGAG CAGTCATGGCAGCTGAGTCC GAG TCC GCA GCA GGT G CCCTCACACTCAGATCATCTTCT TAGTCCTTCCTACCCCAATTTCC GCATCCACGTGTTGGCTCA GTCTTCAATGTCCGCATCCTG TAGGTGCCCCCAATTTCATC GTG TCA GAG TCC ATG GGA GCTACGACGTGGGCTACAG TTGGTCCTTAGCCACTCCTTC CTCCAGCCTACTCATTGGGATCA oxidative, and anti-inflammatory effects [11,13,16,24]. Table 1.…”
Section: Introductionmentioning
confidence: 99%